Circulating growth factors and cardiac remodeling in the community: The Framingham Heart Study. (15th April 2021) - Castro-Diehl, Cecilia; Song, Rebecca J.; Sawyer, Douglas B.; Wollert, Kai C.; Mitchell, Gary F.; Cheng, Susan; Vasan, Ramachandran S.; Xanthakis, Vanessa
Abstract: Background and aims: Cardiac and vascular growth factors (GF) may influence myocardial remodeling through cardiac growth and angiogenic effects. We hypothesized that concentrations of circulating GF are associated with cardiac remodeling traits. Methods: We related blood concentrations of vascular endothelial GF (VEGF), VEGFR-1 (sFlt1), angiopoietin 2 (Ang-2), soluble angiopoietin type-2 receptor (sTie2), hepatocyte GF (HGF), insulin-like GF (IGF)-1, IGF binding protein (IGFBP)-3, and growth differentiation factor-15 (GDF-15) to echocardiographic traits in 3151 Framingham Study participants (mean age 40 years, 55% women). We evaluated the following measures: left ventricular (LV) mass index (LVMi), LV ejection fraction (LVEF), global longitudinal strain (GLS), mitral E/e', and aortic root diameter (AoR). All biomarker values were sex-standardized. Results: In multivariable-adjusted analyses, higher GDF-15 concentrations were associated with higher log-LVMi (β = 0.009 per SD, P = 0.01). Similarly, sTie2 concentrations were positively associated with log-E/e' (β = 0.011 per SD, P = 0.04). IGF-1 and Ang-2 concentrations were positively and negatively associated with GLS, respectively (βIGF-1 = 0.16 per SD and βAng-2 = −0.15 per SD, both P < 0.05), whereas higher sFlt1 and Ang-2 levels were associated with smaller log-AoR (βsFlt1 = −0.004 per SD and β Ang-2 = −0.005 per SD, respectively; P < 0.05). Conclusion: In our large community-based sample, we observed patterns of associations between several circulating vascular GF and cardiac remodeling indices that are consistent with the known biological effects of these pro- and anti-angiogenic factors on the myocardium and conduit arteries. Additional studies are warranted to replicate our findings and assess their prognostic significance. Highlights: There are patterns of associations between several circulating vascular GF and cardiac remodeling. The findings are consistent with the known biological effects of these pro- and anti-angiogenic factors on the myocardium and conduit arteries. Additional studies are warranted to replicate our findings and assess their prognostic significance.